2016
DOI: 10.1098/rsos.150711
|View full text |Cite
|
Sign up to set email alerts
|

A scenario for the evolution of selective egg coloration: the roles of enemy-free space, camouflage, thermoregulation and pigment limitation

Abstract: Behavioural plasticity can drive the evolution of new traits in animals. In oviparous species, plasticity in oviposition behaviour could promote the evolution of new egg traits by exposing them to different selective pressures in novel oviposition sites. Individual females of the predatory stink bug Podisus maculiventris are able to selectively colour their eggs depending on leaf side, laying lightly pigmented eggs on leaf undersides and more pigmented eggs, which are more resistant to ultraviolet (UV) radiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Populations of African village weaverbirds Ploceus cucullatus changed in egg appearance after being introduced in sites where they experienced different levels of solar radiation compared to those in their original sites (Lahti, ). However, the variation described in these studies can also be interpreted either as local adaptation (evolution), or environmental constraints affecting egg coloration by modifying the state (nutritional status/stress level) of the female bird, and it remains to be demonstrated whether birds plastically adjust egg coloration to match environmental conditions, as it has been shown in insects (Abram et al., ; Torres‐Campos, Abram, Guerra‐Grenier, Boivin, & Brodeur, ). Individual phenotypic plasticity may be adaptive, as there may be differences in the effects of solar radiation throughout the long nesting season of the Kentish plover (individual females may lay up to four clutches in a season [Fraga & Amat, ]), as well as between sites at which individual plovers may breed during successive nesting attempts.…”
Section: Discussionmentioning
confidence: 92%
“…Populations of African village weaverbirds Ploceus cucullatus changed in egg appearance after being introduced in sites where they experienced different levels of solar radiation compared to those in their original sites (Lahti, ). However, the variation described in these studies can also be interpreted either as local adaptation (evolution), or environmental constraints affecting egg coloration by modifying the state (nutritional status/stress level) of the female bird, and it remains to be demonstrated whether birds plastically adjust egg coloration to match environmental conditions, as it has been shown in insects (Abram et al., ; Torres‐Campos, Abram, Guerra‐Grenier, Boivin, & Brodeur, ). Individual phenotypic plasticity may be adaptive, as there may be differences in the effects of solar radiation throughout the long nesting season of the Kentish plover (individual females may lay up to four clutches in a season [Fraga & Amat, ]), as well as between sites at which individual plovers may breed during successive nesting attempts.…”
Section: Discussionmentioning
confidence: 92%
“…The fact that the black markings absorb UV radiation while the white markings reflect it suggests that the embryos are probably protected against ionizing radiation. Podisus maculiventris (Say 1832), another stink bug, is known to have evolved selective egg pigmentation as a way to cope with UV radiation (Abram et al, 2015b) and predation (Torres-Campos et al, 2016), a trait that is recycled by its egg parasitoids (Gaudreau et al, 2017). Farnesi et al (2017) have also shown that higher levels of melanisation in mosquito eggs are inversely correlated to egg desiccation; such a function could also be served by the pigment in the Harlequin bug eggs.…”
Section: Discussionmentioning
confidence: 99%
“…Although this paper looked at the three likely derived egg-laying strategies (PT, NT and PB) as evolving simultaneously, this may not have been the case in nature. Indeed, -Campos et al (2016) suggested that selective egg pigmentation evolved after the selective oviposition site choice, implying that NT disappeared at some point in favor of PT and PB, only to eventually reappear and replace PB. In such a scenario, the cost of pigmentation may have been the key selective pressure in the evolution of color polymorphism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations